Cross-Dehydrogenative Coupling Reactions for the Functionalization of α-Amino Acid Derivatives and Peptides - Segundo, Marcos San; Correa, Arkaitz (Synthesis, 2018)
The functionalization of typically unreactive C(sp3)–H bonds holds great promise for reducing the reliance on existing functional groups while improving atom-economy and energy efficiency. As a result, this topic is a matter of genuine concern for scientists in order to achieve greener chemical processes. The site-specific modification of α-amino acid and peptides based upon C(sp3)–H functionalization still represents a great challenge of utmost synthetic importance. This short review summarizes the most recent advances in ‘Cross-Dehydrogenative Couplings’ of α-amino carbonyl compounds and peptide derivatives with a variety of nucleophilic coupling partners.1 Introduction2 C–C Bond-Forming Oxidative Couplings2.1 Reaction with Alkynes2.2 Reaction with Alkenes2.3 Reaction with (Hetero)arenes2.4 Reaction with Alkyl Reagents3 C–Heteroatom Bond-Forming Oxidative Couplings3.1 C–P Bond Formation3.2 C–N Bond Formation3.3 C–O and C–S Bond Formation4 Conclusions
Keywords: cross-dehydrogenative coupling; peptide; α-amino acid; oxidative; C–H functionalization